The Influence of School Principal Leadership, School Committee Roles, and Teacher’s Pedagogical Competence on the Quality of Public High School in Blora Regency - Puspitasari, Rahmayanti; Soedjono, Soedjono; Prayito, Muhammad (Electronic Journal of Education, Social Economics and Technology, 2024)
This study was motivated by the low quality of public senior high schools in Blora Regency, as indicated by the decline in educational report scores on literacy, numeracy, and character indicators, as well as suboptimal academic and non-academic achievements. The main factors influencing this issue include ineffective school principal leadership, the suboptimal role of the school committee, and low teacher pedagogical competence. This research employed a quantitative approach, with a population comprising all public senior high school teachers in Blora Regency and a sample of 206 teachers. Data were collected using closed-ended questionnaires and analyzed through normality, linearity, homogeneity, and multicollinearity tests, followed by hypothesis testing using simple and multiple regression analyses. The findings indicate that school principal leadership affects school quality by 56.2% (correlation coefficient 0.749), the role of the school committee by 34.4% (correlation coefficient 0.587), and teacher pedagogical competence by 43.3% (correlation coefficient 0.658). Simultaneously, these three variables influence school quality by 61.1% (correlation coefficient 0.782). These results highlight the crucial role of school principals, school committees, and teachers in improving educational quality.